143k views
16 votes
Solve:


(6x + 1)/(3) + 1 = (x - 3)/(6)
→ Don't plagiarism
→ Perfect answer needed. ​

2 Answers

9 votes

Explanation:


(6x + 1)/(3) + 1 = (x - 3)/(6) \\ (6x + 1 + 3)/(3) = (x - 3)/(6) \\ 6( 6x + 4) = 3(x - 3) \\ 36x + 24 = 3x - 9 \\ 36x - 3x = - 9 - 24 \\ 33x = - 33 \\ x = - 1

User Jfga
by
5.1k points
8 votes


\qquad\qquad\huge\underline{{\sf Answer}}☂

Let's solve ~


\qquad \sf  \dashrightarrow \: (6x + 1)/(3) + 1 = (x - 3)/(6)


\qquad \sf  \dashrightarrow \: (6x + 1)/(3) - (x - 3)/(6) =- 1


\qquad \sf  \dashrightarrow \: (12x + 2 - x + 3)/(6) =- 1


\qquad \sf  \dashrightarrow \: (11x + 5)/(6) =- 1


\qquad \sf  \dashrightarrow \: {11x + 5}{} =- 6


\qquad \sf  \dashrightarrow \: 11x = -6 - 5


\qquad \sf  \dashrightarrow \: x = -1

User Marsellus Wallace
by
4.7k points